2015
DOI: 10.1017/s0263574715000533
|View full text |Cite
|
Sign up to set email alerts
|

Control distribution of partially decoupled multi-level manipulators with five DOFs

Abstract: SUMMARYMulti-level manipulators are those mechanisms in which two or more levels, that define the main chain of the manipulator, are joined in parallel to each other. Besides, each level is linked to the base in parallel by some limbs. Based on the idea of multi-level manipulators and using the concept of plain leg surfaces, the synthesis of partially decoupled manipulators with five degrees of freedom is presented. Among the different possibilities that exist to design the main chain of the manipulator, one i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Ding et al 12 developed a software for the semiautomated structure synthesis of 5-dof symmetrical and asymmetrical parallel manipulators. Loizaga et al 13 shown that the synthesis of 5-dof partially decoupled manipulators can be achieved combining the idea of multi-level manipulators 14,15 and the concept of plain leg surfaces. Wang et al 16 introduced a 5-dof PM able to perform the 3T2R motion showing a high-rotational capability, an attribute preferred in this kind of robots.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al 12 developed a software for the semiautomated structure synthesis of 5-dof symmetrical and asymmetrical parallel manipulators. Loizaga et al 13 shown that the synthesis of 5-dof partially decoupled manipulators can be achieved combining the idea of multi-level manipulators 14,15 and the concept of plain leg surfaces. Wang et al 16 introduced a 5-dof PM able to perform the 3T2R motion showing a high-rotational capability, an attribute preferred in this kind of robots.…”
Section: Introductionmentioning
confidence: 99%